2019
DOI: 10.1186/s13756-019-0507-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of psychologically tailored hand hygiene interventions on nosocomial infections with multidrug-resistant organisms: results of the cluster-randomized controlled trial PSYGIENE

Abstract: BackgroundProfessional hand hygiene compliance represents a multifaceted behaviour with various determinants. Thus, it has been proposed to apply psychological frameworks of behaviour change to its promotion. However, randomized controlled trials of such approaches, which also assess nosocomial infections (NIs), are rare. This study analyses data of the PSYGIENE-trial (PSYchological optimized hand hyGIENE promotion), which has shown improvements in compliance after interventions tailored based on the Health Ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0
24

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(58 citation statements)
references
References 50 publications
4
30
0
24
Order By: Relevance
“…We observed significantly lower rates of device-associated BSIs in the intervention group when compared to the control group, similar to other studies that have demonstrated a reduction in HAI rates due to improved HH [ 27 29 ]. Despite a focus on PVCs in our teaching materials, this difference was mainly due to a lower rate of CVC-associated BSIs.…”
Section: Discussionsupporting
confidence: 90%
“…We observed significantly lower rates of device-associated BSIs in the intervention group when compared to the control group, similar to other studies that have demonstrated a reduction in HAI rates due to improved HH [ 27 29 ]. Despite a focus on PVCs in our teaching materials, this difference was mainly due to a lower rate of CVC-associated BSIs.…”
Section: Discussionsupporting
confidence: 90%
“…The best way to achieve this is multifocal teaching with mixed methodologies, because it is not completely clear which teaching methods are better than others [52]. However, some systematic reviews have shown that tailored interventions addressing the determinants of practice improve hand hygiene compliance [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Among the other interventions least used (i.e., in below 10% of the studies), tailored interventions, which have, e.g., been shown to be especially effective in promoting hand hygiene compliance and lead to larger reductions in MRE-infections than non-tailored ones [77,78], are particularly noteworthy. Baker and colleagues defined tailored interventions as "… strategies to improve professional practice that are planned, taking account of prospectively identified determinants of practice" [79] (p. 5).…”
Section: Discussionmentioning
confidence: 99%